How cheap is primary health care? Cost per script at the Heidedal Community Health Centre and National District Hospital in Bloemfontein - H. Dippenaar; G. Joubert; C. van Rooyen (South African Family Practice)
Background: It is essential to manage and budget for primary health care in order to deliver a sustainable, accessible and quality health service to the majority of the population. The aim of the study was to establish the cost per script at the Heidedal Community Health Centre (HCHC) and at the National District Hospital (NDH) in Bloemfontein and to evaluate prescribing patterns, the protocols and use of the Essential Drug List (EDL) and Standard Treatment Guidelines (STGs) and to budget more accurately for medicine.